PENDAMPINGAN UMKM MAHASISWA SETU FARM DI ERA PANDEMI - Jaharuddin Jaharuddin; Adi Mansah; Hartutik Hartutik (Media Resonansi Pengabdian Masyarakat, 2025)
The economic crisis has had a significant impact on economic stability, as evidenced by the increasing number of layoffs due to business closures. In response to this challenge, innovation and creativity are essential to creating new business opportunities. Hafiz, a student from the Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Jakarta, addressed this issue by establishing a catfish farming business named "Setu Farm." To support the development of this business, a comprehensive mentoring program was conducted, covering aspects of management, funding, marketing, and business model development. The mentoring process was carried out continuously, from the initial stages to production capacity enhancement through the construction of new ponds and market expansion. The results of this initiative indicate that mentoring-based support can improve operational efficiency and expand the market reach of student-led enterprises.Keywords: Student entrepreneurship, Business mentoring, Business innovation, Catfish farming, Business development